A 115 kDa calmodulin-binding protein is located in rat liver endosome fractions. - Enrich, C (1988)
The distribution of calmodulin-binding polypeptides in various rat liver subcellular fractions was investigated. Plasma-membrane, endosome, Golgi and lysosome fractions were prepared by established procedures. The calmodulin-binding polypeptides present in the subcellular fractions were identified by using an overlay technique after transfer from gels to nitrocellulose sheets. Distinctive populations of calmodulin-binding polypeptides were present in all the fractions examined except lysosomes. A major 115 kDa calmodulin-binding polypeptide of pI 4.3 was located to the endosome subfractions, and it emerges as a candidate endosome-specific protein. Partitioning of endosome fractions between aqueous and Triton X-114 phases indicated that the calmodulin-binding polypeptide was hydrophobic. Major calmodulin-binding polypeptides of 140 and 240 kDa and minor polypeptides of 40-60 kDa were present in plasma membranes. The distribution of calmodulin in the various endosome and plasma-membrane fractions was also analysed, and the results indicated that the amounts were high compared with those in the cytosol.